Ecoart in Action Activities, Case Studies, and Provocations for Classrooms and Communities. - Geffen, Amara (New Village Press, 2022)
"Compiled from 67 members of the Ecoart Network, a group of more than 200 internationally established practitioners, Ecoart in Action stands as a field guide that offers practical solutions to critical environmental challenges. Organized into three sections-Activities, Case Studies, and Provocations-each contribution provides models for ecoart practice that are adaptable for use within a variety of classrooms, communities, and contexts"--